2005
DOI: 10.1162/105474605774918778
|View full text |Cite
|
Sign up to set email alerts
|

Movement Around Real and Virtual Cluttered Environments

Abstract: Two experiments investigated participants' ability to search for targets in a cluttered small-scale space. The first experiment was conducted in the real world with two field of view conditions (full vs. restricted), and participants found the task trivial to perform in both. The second experiment used the same search task but was conducted in a desktop virtual environment (VE), and investigated two movement interfaces and two visual scene conditions. Participants restricted to forward only movement performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 25 publications
(39 reference statements)
2
33
0
Order By: Relevance
“…2): Only 13.9% of the trials were finished without any revisits in the walking condition, and performance did not significantly drop further when physical motion cues were excluded for translations (real rotation condition) and rotations (joystick condition) (cf. % perfect trials (no revisits) Lessels & Ruddle (2005) Ruddle & Table 1. Analysis of variance and planned pairwise contrasts results for the different dependent variables.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2): Only 13.9% of the trials were finished without any revisits in the walking condition, and performance did not significantly drop further when physical motion cues were excluded for translations (real rotation condition) and rotations (joystick condition) (cf. % perfect trials (no revisits) Lessels & Ruddle (2005) Ruddle & Table 1. Analysis of variance and planned pairwise contrasts results for the different dependent variables.…”
Section: Resultsmentioning
confidence: 99%
“…In an important series of studies on navigational search in real and virtual environments, Ruddle and Lessels found that participants performed better when allowed to freely walk, as compared to a "real rotation" condition where they wore an HMD and could freely rotate while controlling simulated translations using a button-based motion model (Lessels & Ruddle, 2005;Ruddle & Lessels, 2006. This real rotation condition led to similar performance as a visual only condition, where both translations and rotations were only visually simulated on a desktop monitor, and controlled via keyboard presses and mouse motions, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples are systems that allow people to share GPS trails for hiking and mountain biking routes (e.g., www.memory-map.co.uk), and browser plug-ins that allow a person to follow a particular search path that someone took on the WWW (e.g., www.trexy.com). In VEs, specific trails have been used to illustrate an individual's path when reporting studies of navigation (e.g., Gamberini, Cottone, Spagnolli, Varotto, & Mantovani, 2003;Lessels & Ruddle, 2005). …”
Section: Generating Trails Automatically 4 2 Automatically Generated mentioning
confidence: 99%